The role of food safety in health and development : report of a Joint FAO/WHO Expert Committee on Food Safety, meeting held in Geneva from 30 May to 6 June 1983 - Joint FAO/WHO Expert Committee on Food Safety; World Health Organization; food and Agricultural Organization of the United Nations (Geneva : World Health Organization, 1984)
Analyses the risks to health and socioeconomic progress posed by biologically or chemically contaminated foods. Unprecedented in the scope of its assessment, the report uses meticulously researched facts and figures to explore the many biological, environmental, and cultural factors that can compromise food safety. The objective is to identify the causes of food contamination, assess their consequences in terms of health and economic productivity, and map out strategies that can reduce their incidence on a global scale. Concise yet thorough in its coverage, the report marks the first major effort to give health planners, policy makers, and members of the food industry a global overview of the causes and consequences of contaminated food, an agenda of research and planning priorities, and a set of workable preventive strategies.
Introduction -- nature and extent of the problem -- Factors affecting the safety of food -- Strategies for improving food safety -- conclusions and recommendations -- Acknowledgements -- Annexes.
Keywords: Food Contamination; Socioeconomic Factors